Status Kepegawaian Guru di Indonesia; ASN PNS-PPPK, NON ASN-GTT-GTY - Varadis, Muhammad Desilva Adis; Noviyanti, Indah Nurul; Tiyaningsih, Seifi; Nugroho, Puspo (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
This study aims to examine the differences between the State Civil Apparatus (ASN) and non-ASN, especially in the teaching profession, as well as their rights and performance. The method used is a literature study, by deeply exploring theories and concepts from various written sources. Analysis is done descriptively and critically to evaluate the available data. ASN includes Civil Servants (PNS) and Government Employees with Work Agreements (PPPK), while non-ASN includes Non-Permanent Teachers (GTT) and Permanent Foundation Teachers (GTY). This article discusses teachers' rights and welfare, as well as performance differences between ASN and non-ASN based on applicable regulations and empirical studies. The results show that employment status affects performance, with civil servant and certified teachers tending to perform better than non-civil servant teachers. This research emphasizes the importance of paying attention to teacher welfare and competency development to improve the quality of education.